PENGARUH STRUKTUR MODAL TERHADAP PERTUMBUHAN LABA PADA BANK BUMN PERSERO (2010-2015) - Hartanti Hartanti (MONETER - JURNAL AKUNTANSI DAN KEUANGAN, 2016)
The capital structure is very important for banking companies, for the management must make the right decision because if the company's capital structure that is bad can cause high capital costs for the company and affect the growth of corporate profits. This study aims to determine the effect of simultaneous and partial capital structure of the Bank BUMN Persero profit growth. As for the research object is owned state-owned bank is the National Bank of Indonesia, Bank Rakyat Indonesia, the State Savings Bank and Bank Mandiri. Data used in the form of financial statements Six years in a row 2010-2015 period ended December 31. The research method uses quantitative methods to the analysis model of multiple linear regression coefficient. Partial use simple regression analysis model, which became the independent variable is the DER (X1), CAR (X2) and the dependent variable profit growth (Y) doped with SPSS 20. The results of this study indicate that capital structure seen from DER ratio and CAR are silmutan effect of 14.5% and no significant effect on earnings growth of state-owned banks, while partially also did not significantly affect the growth of state-owned bank profits. Management must be able to manage its capital structure primarily of capital from debt to improve performance so that debts can be met and the banks should pay attention to capital adequacy that comes from all the bank's assets that contain risks involved be financed from funds own capital of banks in addition to obtaining funds from sources - source outside the bank.  Keywords : Capital Structure, Income Growth